2010
DOI: 10.5539/elt.v3n2p64
|View full text |Cite
|
Sign up to set email alerts
|

Infusing Cooperative Learning into An EFL Classroom

Abstract: This study sought to investigate student diversities in terms of learning styles and linguistic competence, and the extent to which students change as regards participation, interaction and achievement through Cooperative Learning activities embracing their diversities. 77 first-year EFL students from from the two reading classes, one treated as the experimental group (EG) and the other as the control group (CG), at the Faculty of English Linguistics of the University of Social Sciences and Humanities in Ho Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…This may be interpreted as indicating that during group interaction to treat errors, students had to consider many options while if treated by teacher's correction, there would be an obvious and clear explanation and correction. Also, this response may be accounted for by the dependent learning styles and the traditional beliefs in the teacher-oriented authority of students in this context (Nelson & Carson, 1998;Tuan, 2010). That is likely to be 44% of students agreed with the beneficial effects of the teacher's direct correction Themes 2 and 3: Proficiency of correcting and accurate writing (see Table 1) Overall the respondents perceived that CF led to improvement.…”
Section: Focus Of Research Question 1: Attitudes Toward Noticing-basementioning
confidence: 99%
“…This may be interpreted as indicating that during group interaction to treat errors, students had to consider many options while if treated by teacher's correction, there would be an obvious and clear explanation and correction. Also, this response may be accounted for by the dependent learning styles and the traditional beliefs in the teacher-oriented authority of students in this context (Nelson & Carson, 1998;Tuan, 2010). That is likely to be 44% of students agreed with the beneficial effects of the teacher's direct correction Themes 2 and 3: Proficiency of correcting and accurate writing (see Table 1) Overall the respondents perceived that CF led to improvement.…”
Section: Focus Of Research Question 1: Attitudes Toward Noticing-basementioning
confidence: 99%
“…Kao (2003) and Liao (2005) showed that motivation and speaking skills can be enhanced via cooperative learning. Dang (2007), Tuan (2010) and Vo (2010) also conducted various studies on the effectiveness of cooperative learning on the achievements of students in secondary and intermediate levels. The results showed that language skills and students' achievements were improved, interpersonal skills were developed and creative thinking was promoted upon undertaking cooperative learning.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the Vietnamese context, Dang (2007), Pham (2010), Tuan (2010), conducted various studies on cooperative learning among students of secondary and intermediate level where they analysed the experiences and perceptions of students. The results showed that language skills were improved, interpersonal skills were developed and creative thinking was promoted upon undertaking cooperative learning.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve more than simply putting people in groups and asking them to work together, CL activities are based on five basic principles: (a) positive interdependence, (b) individual accountability, (c) equal participation, (d) simultaneous interaction, and (e) group processing (Candlin et al, 2003). The combination of these principles in task design promotes peer interaction and cooperation for studying academic subjects (Tuan, 2010). Each learner in a CL group actively takes part, contributes their ideas and knowledge, and creates groups that both academically and personally support each member (Candlin et al, 2003).…”
Section: Collaborative Learning (Cl)mentioning
confidence: 99%
“…Realizing that our students are not exactly blank slates can be of great benefit to teachers when planning effective CL activities. Most learners assume that it will only be possible to learn from the teacher, and not from the group (Tuan, 2010). Therefore, it is important to be clear about the benefits of the activities and point out the ways in which the activities and group exposure are going to help them to personally improve.…”
Section: And the Toefl Ibtmentioning
confidence: 99%